2014
DOI: 10.3892/mmr.2014.2621
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the SRD5A2 gene and the risk of prostate cancer

Abstract: Abstract. Androgens are actively involved in the development of the prostate gland and appear to be essential for prostate carcinogenesis. The product of the SRD5A2 gene, membrane-bound steroid 5-α-reductase, type II enzyme, is key in testosterone metabolism. The present study explored the association between the SRD5A2 V89L gene polymorphism and the risk of developing prostate cancer. The study cohort consisted of 456 male Slovak patients, including 260 cases with histologically confirmed prostate cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…Therefore, SRD5A2 V89L gene polymorphism has been associated with breast cancer and prostate cancer in previous studies. [26][27][28] In the present study, we found that SRD5A2 was an independent risk factor for RFS in HCC. Liver regulates the metabolism and activity of sex hormones.…”
supporting
confidence: 60%
“…Therefore, SRD5A2 V89L gene polymorphism has been associated with breast cancer and prostate cancer in previous studies. [26][27][28] In the present study, we found that SRD5A2 was an independent risk factor for RFS in HCC. Liver regulates the metabolism and activity of sex hormones.…”
supporting
confidence: 60%
“…The association of this polymorphism with androgenrelated cancer risk is even more controversial. No association between the p.Val89Leu polymorphism and an increased risk of developing prostate cancer was identified among 456 Slovak male patients [Dušenka et al, 2014]. On the contrary, the presence of p.Val89Leu polymorphism has been implicated as a risk for breast cancer development [Francis et al, 2014].…”
Section: Srd5a2 Gene Polymorphismsmentioning
confidence: 96%